2009
DOI: 10.1021/cg900131g
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth and Dissolution of Calcite in the Presence of Fluoride Ions: An Atomic Force Microscopy Study

Abstract: Growth and dissolution of calcite {1014} surfaces in aqueous solutions in the presence of fluoride ions have been studied by in situ atomic force microscopy (AFM). Supersaturated and undersaturated solutions with respect to calcite were prepared for the growth and dissolution experiments, respectively. The concentration range of solutions containing fluoride ions varied between 0.025 and 50 mM. The crystal growth rates were measured from the step growth of closing of etch pits along the [010] direction as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 82 publications
2
26
0
Order By: Relevance
“…The observations presented in this study suggest that the presence of organic ligands negligibly affects calcite dissolution rates. This observation appears to contrast with observations of calcite surfaces during their dissolution by atomic force microscopy; several studies have shown that the presence of trace quantities of dissolved organic and other trace species can dramatically change the shape of etch pits forming and step velocities on calcite surfaces (Teng and Dove, 1997;Astilleros et al, 2002;Arvidson et al, 2006;Harstad and Stipp, 2007;Ruiz-Agudo et al, 2010;Vavouraki et al, 2010;Yoshino et al, 2010). There are several possible reasons for these apparent differences.…”
Section: Relative Effects Of Organic Ligands On Calcite Dissolution Rmentioning
confidence: 72%
“…The observations presented in this study suggest that the presence of organic ligands negligibly affects calcite dissolution rates. This observation appears to contrast with observations of calcite surfaces during their dissolution by atomic force microscopy; several studies have shown that the presence of trace quantities of dissolved organic and other trace species can dramatically change the shape of etch pits forming and step velocities on calcite surfaces (Teng and Dove, 1997;Astilleros et al, 2002;Arvidson et al, 2006;Harstad and Stipp, 2007;Ruiz-Agudo et al, 2010;Vavouraki et al, 2010;Yoshino et al, 2010). There are several possible reasons for these apparent differences.…”
Section: Relative Effects Of Organic Ligands On Calcite Dissolution Rmentioning
confidence: 72%
“…Effect of F À , SO 2À 4 and Li + on growth hillock morphology: surface stabilization due to increased hydration Changes in the morphology of growth features on calcite cleavage surfaces in the presence of NaF and Na 2 SO 4 were previously reported by Vavouraki et al (2008Vavouraki et al ( , 2010. They suggested F À and SO 2À 4 incorporation on specific sites of the calcite surface as the most likely cause of the change in growth morphology.…”
Section: Reversed Geometries Of Calcite Growth Hillocks Induced By Thmentioning
confidence: 73%
“…Steefel and MacQuarrie, 1996;Knauss et al, 2005;Steefel and Maher, 2009;Zhu, 2009;Goddéris et al, 2010;Zhu et al, 2010;Liu et al, 2011), yet the applicability of such models has not been verified in detail and may be inconsistent with what is known about mineral precipitation kinetics (e.g. Nielsen, 1964Nielsen, , 1984Nancollas and Reddy, 1971;Reddy and Nancollas, 1976;Reddy and Gaillard, 1981;Inskeep and Bloom, 1985;Mucci, 1986;Van Cappellen and Berner, 1991;Piana et al, 2006;Kowacz et al, 2007;Vekilov, 2007;Bénézeth et al, 2008;Kowacz and Putnis, 2008;Perdikouri et al, 2009;Vavouraki et al, 2010;RodriguezBlanco et al, 2011). In an attempt to explore the link between dissolution and precipitation, magnesite precipitation rates have been measured as a function of chemical affinity and aqueous solution composition using the same solids and experimental methods as used by Saldi et al (2010) for magnesite dissolution.…”
Section: Introductionmentioning
confidence: 99%